Pembatasan Hak Veto dalam DK-PBB Terkait Konflik Bersenjata di Suriah - Danang Wahyu Setyo Adi (CV Rewang Rencang, 2020)
The United Nations (UN) is a new international order organization formed after the failure of the Post-World War League of Nations (LBB). Within the UN, there are important organs, one of which is the Security Council with five permanent members including the United States, Britain, Russia, France and China. The five permanent members have the authority to issue veto power over the policies to be established. One of them is the policy of issuing resolutions to the case of armed conflict in Syria. This paper will discuss in more depth the policy of the resolution in view of international legal sources and related theories. Included in this regard are the authors criticizing the conception of veto power attached to the five permanent member states of the UN Security Council which should be aimed and used to achieve world peace and not for any particular interest.